Response of farmed fallow deer to human presence - Janiszewski, Paweł; Steiner-Bogdaszewska, Zaneta (Polish Journal of Natural Sciences, 2022)
Direct behavioural responses to human presence are a very important consideration in red deer and fallow deer farming. Farm employees performing daily operations and visitors (agritourism) can trigger unexpected animal behaviours, elicit antagonistic responses or even contribute to accidents. Therefore, the aim of this study was to describe the behavioural responses of farm-raised fallow deer to the presence of strangers in the direct vicinity of the grazing paddock. Two independent behavioural tests were designed to analyse the responses of individual animals to a person or a group of people in the immediate vicinity. The results of a three-way analysis of variance revealed a significant main effect of the number of observers, which points to differences between groups, regardless of the animal’s sex and observation date. Fallow deer were more agitated in the presence of individuals than groups of people. It is important for the maintenance of animal welfare, both during routine work on the farm and during the observation of their health.